(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the effect of trans-anethole in combination with methotrexate, compared to monotherapy with trans-anethole or methotrexate, on inflammatory parameters and oxidative stress of arthritic rats. The experimental model of arthritis induced by Freund’s complete adjuvant (AIA) in rats was used. Treatment with trans-anethole and methotrexate, in combination or monotherapy, was started on the day of AIA induction and continued for 21 days. The association of anethole (62.5 mg/Kg) to methotrexate (6 mg/Kg) therapy was able to further reduce both the oxidative stress induced by arthritis and the inflammatory events that characterize the disease, as demonstrated by the following indicators: 1) decrease in the edema of the hind legs, in the score of secondary lesions, in the recruitment of leukocytes to the articular cavity and in the plasma myeloperoxidase activity; 2) increase in plasma content of reduced thiols and total antioxidant capacity; 3) diminution of protein carbonylation in plasma, liver and kidneys; 4) decrease in lipid peroxidation in the liver; 5) reduction in the hepatic ROS content; 6) enhancement of the activity of the antioxidant enzymes and GSH/GSSG ratio. In general, the combination anethole + methotrexate presented a substantially higher effect than the monotherapy with anethole or methotrexate (at the same doses). The data obtained in this work allow us to conclude that the use of trans-anethole in combination with methotrexate suppressed arthritic progression in rats, with the main advantage of reduction of methotrexate dose, attenuating adverse effects caused by high dose therapy.